Changes in the Behaviour of Tourist Consumers on the Polish-Czech Border During Crises. Generational Context - Dědková, Jaroslava; Gryszel, Piotr; Michalska-Dudek, Izabela (Publishing House of Wroclaw University of Economics and Business, 2025)
The study aimed to examine the impact of crises in the years 2019-2024 (such as the COVID-19 pandemic, the war in Ukraine, inflation, and the energy crisis) on the tourist behaviour of residents of the Polish-Czech border from a generational perspective. The study used the CAWI method on a sample of 717 respondents representing generations BB, X, Y, and Z from the Nysa Euroregion. The results indicated significant intergenerational differences in how people responded to crises. Generation Z was the most flexible and resistant to change, while generations BB and X chose significantly limited long-distance travel, preferring domestic and cross-border destinations. In particular, interest in cross-border travel among Czechs has increased, which can be explained by the relative difference in inflation and purchasing power compared to Poland. Research shows domestic and cross-border travel to neighbouring countries remains the most stable tourist activity during crises.
Quote as: Dědková, J., Gryszel, P., & Michalska-Dudek, I. (2025). Changes in the Behaviour of Tourist Consumers on the Polish-Czech Border During Crises. Generational Context. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), Sustainable Development in Light of Research by Scientists from Poland, Czechia and Slovakia. Different Research Perspectives (pp. 208-216). Publishing House of Wroclaw University of Economics and Business.
Keywords: tourism in crisis; consumer behaviour; generations; Euroregion Nysa; cross-border tourism